2016
DOI: 10.1007/s00344-016-9598-x
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Mercury Toxicity in Wheat by the Interaction of Mercury-Tolerant Plant Growth-Promoting Rhizobacteria

Abstract: Heavy metal contamination of agricultural soils has increased along with industrialization. Mercury is a toxic heavy metal and a widespread pollutant in the ecosystem. Mercury-tolerant and plant growth-promoting rhizobacteria (PGPR) HG 1, HG 2, and HG 3 were isolated from the rhizosphere of plants growing in a mercury-contaminated site. These isolates were able to grow in the presence of mercury ranging from 10 to 200 lM in minimal medium and 25 to 500 lM in LB medium. The strains were characterized by morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“…However, QA1 showed a higher performance in producing siderophores compared to QF11 ( Figure 3 ). Siderophores are known to enhance P availability [ 9 ], as they solubilize minerals and chelate heavy metals, which in turn increases nutrient uptake and plant growth [ 66 ]. Whipps in 2001 reported that the low iron availability in soil would suppress plant pathogenic fungi [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, QA1 showed a higher performance in producing siderophores compared to QF11 ( Figure 3 ). Siderophores are known to enhance P availability [ 9 ], as they solubilize minerals and chelate heavy metals, which in turn increases nutrient uptake and plant growth [ 66 ]. Whipps in 2001 reported that the low iron availability in soil would suppress plant pathogenic fungi [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, our results support the role of IAA in inducing morphological changes, increased length of the root as well as number of root hairs/laterals, which are crucial for nutrient uptake [ 88 ]. In addition, Bacillus , Pseudomonas and Enterobacter applied as bioinoculants promote plant growth and biomass through production of phytohormones (e.g., auxins and cytokinins) [ 66 , 89 ]. In this aspect, growth and grain yield improvement of wheat plants were associated with PSB inoculation and phytohormone-producing strains such as Azospirillum , Bacillus and Enterobacter [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mercury is one of the most dangerous heavy metals for plants with phytotoxic properties that cause redox imbalance, change in photosynthetic activity, impair growth rate, and a decrease in production (Cui et al, 2015;Gontia-Mishra et al, 2016;Zhang et al, 2017). The high amount of mercury accumulation in plants leads to the death of cells and tissues (Sahu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, mercury ions can replace the magnesium of photosynthetic pigments and interfere with electron transport in chloroplasts, affecting photosynthesis and oxidative metabolism [ 117 , 118 ], which may explain reduction of the growth of A . fluminensis under the effect of mercury, especially in the reduction of the chlorophyll (approximately 70%) in non-inoculated plants.…”
Section: Discussionmentioning
confidence: 99%